Pengaruh Tingkat Literasi Keuangan terhadap Pengelolaan Keuangan pada Pelaku UMKM Binaan Rumah Kreatif BUMN - Dita Harinda Saskia; Yulhendri Yulhendri (Jurnal Ecogen, 2020)
This research was conduct to determine the effect of financial literacy includes financial knowledge, financial skills, and financial attitudes towards financial management in the UMKM guided by Padang BUMN Creative House”. Issues regarding financial management are a key factor that can lead to failure of UMKM. UMKM’s financial management should apply practical and effective methods in financial management by practicing accounting well to make financial information for decision making. This type of research is causal-comparative. The population in this study was the UMKM practitioners guided by BUMN Creative Houses with a total population of 287 UMKM and 75 UMKM as samples. Sampling was determined using the Slovin formula with random sampling techniques. Data collection techniques used in this study were questionnaires. The validity test uses SPSS version 20 seen in the Corrected item-total Correlation column and the reliability test seen in the“Cronbach Alpha” column. The data analysis technique” used multiple linear regression. To test the hypothesis the F test and the T-test were used, using SPSS 20 program. The results are (1) financial knowledge, financial skills, and financial attitudes, that all have a significant and positive influence on financial management in the UMKM of Padang BUMN Creative Houses. (2) financial knowledge has a positive and significant influence on financial management in the UMKM guided by Padang BUMN Creative Houses. (3) financial skills have a positive and significant influence on financial management in the UMKM guided by Padang BUMN Creative Houses. (4) financial attitudes have a positive and significant influence on financial management in the UMKM guided by Padang BUMN Creative Houses. Keywords : financial knowledge, financial skills, ‘financial attitudes